2018
DOI: 10.4236/health.2018.1010106
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Sexual Awareness among High School Students in Tokyo, Japan—Cross Sectional Analysis in Relation to Social Capital

Abstract: Purpose: The study aimed to clarify the relationship between cognitive social capital and sexual awareness in high school students in Tokyo, Japan. Method: The self-administered questionnaire survey was administered to 1073 high school junior students in Tokyo in Feb. 2017 (collection rate 94.5%). Final analysis subjects totaled 1011 boys and girls (94.2%). True/false questions on timing to wear condom for sex knowledge, acceptability to sexual behavior of high school students for sexual awareness, sense of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Other than Watanabe et al's work among high school students in Hanoi and Ho Chi Minh City, Vietnam, and Tokyo, Japan [16][17][18][19] , there is a dearth of previous analyses of the associations between sexual awareness and various factors, particularly SE and SC. In the studies conducted by Watanabe et al, it was found that SC has a stronger association with sexual awareness than sex education or SE, and those with high cognitive SC were likely to have healthy sexual awareness in both cities in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than Watanabe et al's work among high school students in Hanoi and Ho Chi Minh City, Vietnam, and Tokyo, Japan [16][17][18][19] , there is a dearth of previous analyses of the associations between sexual awareness and various factors, particularly SE and SC. In the studies conducted by Watanabe et al, it was found that SC has a stronger association with sexual awareness than sex education or SE, and those with high cognitive SC were likely to have healthy sexual awareness in both cities in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Both structural SC and cognitive SC influence people’s awareness and behavior 14 , 15 ) . Watanabe and colleagues hypothesized that cognitive SC might impact adolescent sexual awareness and tested this hypothesis using questionnaire surveys in Vietnam and Japan 16 , 17 , 18 , 19 ) . Their findings confirmed that adolescent sexual awareness is more likely to be impacted by SC factors such as sense of belonging to the community, rather than by the individual’s sexual knowledge, SE, and the presence of sexually experienced peers—factors that had previously been identified as important 11 , 20 ) .…”
Section: Introductionmentioning
confidence: 99%